KOALISI DAN PENGELOLAAN KOALISI, PADA PEMERINTAHAN JOKO WIDODO-JUSUF KALLA - Efriza Efriza (Populis : Jurnal Sosial dan Humaniora, 2018)
This paper discusses the relationship between the President and the House of Representatives and the coalition government based on the three years of President Joko Widodo (Jokowi), who was trapped in inter-institutional competition as a consequence of a mixture of presidential and multi-party systems.Initialy, President Jokowi has the desire to realize a coalition based on ideology and the same program (consensus coalition) between political parties, but the reality, it is difficult to make it happen in government, finally President Jokowi re-elected a coalition of “all parties”. Using some of the basics of Scott Mainwaring and David Altman about presidential and multiparty combination systems and coalitions in presidential systems, complemented by several Coalitions. Then, complete the results of Otto Kirchheimer on Catch All Party, to outline the transformation of the party in this modern era. Accompanied by discussions on political parties in Indonesia, based on Yasraf Amir Piliang's description of political nomadism. Based on the facts and outcomes, a combination of presidential and multiparty systems and the government's management of government by President Jokowi, which manages a "fat" coalition with accommodative leadership and transactional performances. Matters relating to the harmonious relationship between the President and the House of Representatives with the consequence that the President is committed to realizing an unconditional coalition and not for the power-seats. Coalition management can be done because the choice of the party that develops as a supporter of the government is also based not only on the need for political imagery in order to encourage electoral in the political market, but also in the spirit of the party.                                                                                                                                                         Keywords: Presidential System, Coalition Government, the President-Parliament Relations, Leadership Jokowi